Evaluating listening effort with electroencephalography in ecological situations - Seifi Ala, Tirdad (2022)
Listening effort is the deliberate allocation of mental resources to carry out a listening task. Spending effort can be rewarding if it yields desired results but to invest listening effort constantly will lead to negative consequences such as fatigue, difficulties in speech recall, and social disengagement, especially for hearing-impaired individuals.